ANALYSIS OF THE PROJECT BASED LEARNING LEARNING MODEL BY UTILIZING YOUTUBE MEDIA TO IMPROVE STUDENTS' SPEECH SKILLS AT SMP NEGERI 3 MERAUKE - Mudatsir, Mudatsir; Wahyuniar, Wahyuniar (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to analyze the project-based learning model (PjBL) using YouTube video media in student speech learning. The research subjects were carried out on class IX students in the odd semester of 2023. The research was carried out at SMP Negeri 3 Merauke, with a total of 37 students and the object of this research was speech skills. Data collection techniques use initial tests (pretest) and final tests (posttest), observation, and documentation. Data collection in this research was carried out by conducting tests, namely students' speeches before and after using YouTube media with reference to linguistic and non-linguistic aspects. The results of the research show that the use of YouTube media can improve speech skills and is very effective in teaching speeches for class IX students of SMP Negeri 3 Merauke with the results of comparing the average scores of students in the pretest and posttest with test statistics. t. It is known that the t-value obtained by t-test analysis is -8.627 with a standard deviation value of 7.260 and a p-value of 0.000. This means that there is an influence of the use of YouTube media on improving the speech skills of class XI students at SMP Negeri 3 Merauke.